2003
DOI: 10.1176/appi.ps.54.7.1012
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Assaultive Behavior Among Psychiatric Inpatients

Abstract: Information obtained from interviews with assailants can reveal the underlying causes of specific assaults. This information is potentially useful in the selection of rational antiaggressive treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 9 publications
6
118
2
3
Order By: Relevance
“…Using the sample of 248 men with schizophrenia described above, we found that clinical ratings of deficient affective experience (shallow affect, callousness, lack of remorse and a failure to accept responsibility for one's own actions) was associated with violent offending and with negative symptoms, but not with CD or substance misuse (Sunak 2006). Similarly, in a study of persistently aggressive inpatients, three distinct groups were identified, one of which was characterized by a lack of remorse (Nolan et al 2003). We hypothesize that among patients with schizophrenia, deficient affective experience may be a state that fluctuates as do psychotic symptoms, and that when present it increases the vulnerability for aggressive behaviour towards others.…”
Section: Type III Offenders With Schizophreniamentioning
confidence: 91%
“…Using the sample of 248 men with schizophrenia described above, we found that clinical ratings of deficient affective experience (shallow affect, callousness, lack of remorse and a failure to accept responsibility for one's own actions) was associated with violent offending and with negative symptoms, but not with CD or substance misuse (Sunak 2006). Similarly, in a study of persistently aggressive inpatients, three distinct groups were identified, one of which was characterized by a lack of remorse (Nolan et al 2003). We hypothesize that among patients with schizophrenia, deficient affective experience may be a state that fluctuates as do psychotic symptoms, and that when present it increases the vulnerability for aggressive behaviour towards others.…”
Section: Type III Offenders With Schizophreniamentioning
confidence: 91%
“…In previous papers, aggression had been categorized as ofensive and defensive such as a dangerous or evasive response to a sense of fear, the most frequently preferred classiication in the recent literature categorized into three groups: impulsive, proactive (also known as organized, instrumental, or predatory), and psychotic. Impulsive aggression (54%) is the most common category followed by proactive aggression (29%), and psychotic aggression (17%) [27,28]. As predicted, psychotic aggression is a process related to positive symptoms of psychosis, such as hallucinations or delusional content.…”
Section: Aggressionmentioning
confidence: 79%
“…In proactive aggression, the individual exhibits this behavior in a planned manner to achieve a blazing beneit such as money or revenge. Impulsive aggression is a behavioral patern which is accompanied by physical symptoms after stimulation of the sympathetic system, often associated with feelings of fear, inhibition, or anger, which are manifested by stress, threat, or provocation [28].…”
Section: Aggressionmentioning
confidence: 99%
“…[43] Swanson ve arkadaşları tedavi uyumu gösteren şizofreni tanılı hastalarda şiddet davranışının yalnızca antisosyal kişilik bozukluğu olduğu durumlarda izlendiğini bildirmişlerdir. [44] Kişilik bozukluğu olan şizofreni tanılı hastalarda, tedavi uyumu olan ve olmayan hastaların, şiddet davranışı açısından anlamlı fark gös-termediği izlenmiştir.…”
Section: Klinik öZelliklerunclassified